The road ahead for Construction Grammar - Hilpert, Martin (My University, 2024)
What does the future hold for Construction Grammar? What are the most promising future avenues for research on constructions? This paper addresses the development of Construction Grammar as a theory of language through the perspective of six recent PhD dissertations that explore constructional meaning, the architecture of the constructional network, and the role of language change in a constructional theory of language. The goal of this paper is to establish connections between these ideas, and to spell out how different questions concerning Frame Semantics, distributional semantic methods, priming, nodes and connections, individual differences, and constructional change all contribute to a picture that is bigger than the sum of its parts.